Introduction to the Special Issue of Plants on “Advances in Plant Reproductive Ecology and Conservation Biology” - Brenda Molano-Flores; James I. Cohen (Plants, 2024)
Plant reproductive ecology explores aspects of the biology and ecology of plants ranging from breeding systems, plant–pollinator interactions, seed germination, floral traits, and much more [...]